A study of method development and validation for estimation of Azelastine hydrochloride in nasal spray formulations by RP-HPLC method: A STUDY OF METHOD DEVELOPMENT AND VALIDATION FOR ESTIMATION OF AZELASTINE HYDROCHLORIDE - Gill, Charansingh H.; Kulkarni, Pankaj N; NIPATE, AMOL S; Jadhav, Chetan K; Chate, Asha V; Dodake-Supekar, Alaknanda M (Journal of Drug Delivery and Therapeutics, 2018)
A simple reverse-phase HPLC method for the estimation of Azelastine hydrochloride in nasal spray formulations has been developed. The method is simple, accurate, precise, specific and linear over the analysis range. This developed method has been validated according to International Conference on Harmonization (ICH) guideline with respect to system suitability, specificity, precision, linearity, accuracy, and robustness. An isocratic condition of mobile phase comprising Phosphate buffer (pH 3.1): Acetonitrile in a ratio of 60:40, v/v at a flow rate of 1.0 mL/minute over RP C18 (octadecylsilane (ODS), 250 × 4.6 mm, 5 µm, CHROMOSIL) column at ambient temperature was maintained. Besides, the chromatographic peak was observed sharp & symmetric. The proposed method was successfully applied for the estimation of the Azelastine hydrochloride in nasal spray formulation.